(NzAGADKOWA eLXZA (B:s (NROMAN (B/s - (NsEN^IK(B, (NoLEG rOMANOWI^(B.s ((N~ERN)QÆWCÆ (B:s)E [(NB(B. (NW(B.],s, 2010)
(N~ERGOWIJ ROMAN oLEGA sEN^IKA(B, (NZNANOGO NA bUKOWIN)QÆ PISXMENNIKA(B, (NWIDANIJ U ~ERNÆWCQH (B2010 (NR(B., (NCÆKAWIJ POGLQDOM AWTORA(B-(N^OLOWÆKA NA VÆNO^U SUTX(B, (NPSIHOLOGÆ@ SPRIJNQTTQ ZRADI VÆNKO@(B. (Nl@BOW eLXZI WELIKA(B, (NQK NEBO(B. "çÇ (NNE HWIL@Ã OSUD OTO^U@^IH(B. (NwONA(B, (NNÆBI PRI^INNA(B, (NVIWE SWOÇMI PO^UTTQMI(B. (NdUMKI OBROSTA@TX SUM(B'(NQTTQM UVE BEZ WSQKIH SPODÆWANX(B. (NbO GIDKO DOMAGATISX ^OLOWÆKA(B, (NQKOMU TI BAJDUVA(B..."s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpROZA(B.s; (N~ERN)QÆWECXKIJ AWTOR(B.s)E